Self-motion Manifolds of an 8-DOF Non-holonomic Mobile Manipulator - 姚玉峰 赵建文 孙立宁 (Dong Hua da xue xue bao. Zi ran ke xue ban., 2010)
For the non-holonomic constraint robot,determining the pose of its end-effector will rely on its joints＇ displacement and the velocity of its non-holonomic constraint joints as well.Therefore,it becomes increasingly difficult to obtain the analytic solution of its self-motion manifold in the traditional way for solving matrix equation.In this paper,we take the pose of end manipulator as the result of the joint sequential motion based on the mentality of motion equivalence,the structure and the reference velocity which correspond precisely to the points in self-motion manifold as self-motion variable.Thus an analytical solution for the self-motion manifold of the 8 degree of freedom wheeled mobile manipulator is presented by taking vector algebra as a tool,which facilitates deriving the closed solution of its self-motion manifold.In the closing part of this paper,calculating examples of self-motion manifold and mechanism self-motion simulation are proposed,which proves the validity of solution algorithm for self-motion manifold.